Predicament of English Translation Dilemma in Academia: An Analysis on Selected Scriptures and Traditional Books - Yaacob, Solehah (Journal of Al-Tamaddun, 2022)
Translation is a tool of knowledge transferring an original language to another language. In other words, it is the process of converting the written word from one language into another language in a way that is culturally and linguistically appropriate so it can be understood. There are, however, challenges in translation which include knowing about a variety of features such as the language structure which differs between languages. The combination between the meaning and the written words in the original text has to be interpreted carefully in order to be translated accurately. Unfortunately, some translated works do not comply with the original one. Therefore, to address the problem above, the research attempts to highlight two types of critical translations in the academia: The Scriptures and the Traditional Arabic books through analytic and critical approaches. This paper focuses on an analytical study on some translations from the Bible and Arabic Traditional books with attempt to review and revisit some issues which are related to religion and beliefs as a starting point to the dilemma of translation.